Prevalence of inflammatory heart disease among professional athletes with prior COVID-19 infection who received systematic return-to-play cardiac screening - Martinez, M. W.; Tucker, A. M.; Bloom, O. J.; Green, G.; DiFiori, J. P.; Solomon, G.; Phelan, D.; Kim, J. H.; Meeuwisse, W.; Sills, A. K.; Rowe, D.; Bogoch, I. I.; et al. (JAMA Cardiology, 2021)
IMPORTANCE The major North American professional sports leagues were among the first to return to full-scale sport activity during the coronavirus disease 2019 (COVID-19) pandemic. Given the unknown incidence of adverse cardiac sequelae after COVID-19 infection in athletes, these leagues implemented a conservative return-to-play (RTP) cardiac testing program aligned with American College of Cardiology recommendations for all athletes testing positive for COVID-19. OBJECTIVE To assess the prevalence of detectable inflammatory heart disease in professional athletes with prior COVID-19 infection, using current RTP screening recommendations. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study reviewed RTP cardiac testing performed between May and October 2020 on professional athletes who had tested positive for COVID-19. The professional sports leagues (Major League Soccer, Major League Baseball, National Hockey League, National Football League, and the men`s and women`s National Basketball Association) implemented mandatory cardiac screening requirements for all players who had tested positive for COVID-19 prior to resumption of team-organized sports activities. EXPOSURES Troponin testing, electrocardiography (ECG), and resting echocardiography were performed after a positive COVID-19 test result. Interleague, deidentified cardiac data were pooled for collective analysis. Those with abnormal screening test results were referred for additional testing, including cardiac magnetic resonance imaging and/or stress echocardiography. MAIN OUTCOMES AND MEASURES The prevalence of abnormal RTP test results potentially representing COVID-19-associated cardiac injury, and results and outcomes of additional testing generated by the initial screening process. RESULTS The study included 789 professional athletes (mean [SD] age, 25 [3] years; 777 men [98.5%]). A total of 460 athletes (58.3%) had prior symptomatic COVID-19 illness, and 329 (41.7%) were asymptomatic or paucisymptomatic (minimally symptomatic). Testing was performed a mean (SD) of 19 (17) days (range, 3-156 days) after a positive test result. Abnormal screening results were identified in 30 athletes (3.8%; troponin, 6 athletes [0.8%]; ECG, 10 athletes [1.3%]; echocardiography, 20 athletes [2.5%]), necessitating additional testing; 5 athletes (0.6%) ultimately had cardiac magnetic resonance imaging findings suggesting inflammatory heart disease (myocarditis, 3; pericarditis, 2) that resulted in restriction from play. No adverse cardiac events occurred in athletes who underwent cardiac screening and resumed professional sport participation. CONCLUSIONS AND RELEVANCE This study provides large-scale data assessing the prevalence of relevant COVID-19-associated cardiac pathology with implementation of current RTP screening recommendations. While long-term follow-up is ongoing, few cases of inflammatory heart disease have been detected, and a safe return to professional sports activity has thus far been achieved.